Pengaruh Pemberian Pakan Alami yang Berbeda terhadap Pertumbuhan Berat Mutlak Benih Ikan Lele Mutiara (Clarias gariepinus) Umur 5 Hari - Retno Farianti; Sri Oetami Madyowati; Achmad Kusyairi (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Pearl catfish (Clarias gariepinus) has advantages when cultivated, namely fast growth, efficient feed, has a uniform size and is resistant to disease (Matasina and Sartika, 2020). The success of a fish farming business can be determined by its feeding management, because feed that is consumed effectively by fish can make fish experience good growth (Hanief, et.al, 2014).The purpose of this study was to determine the effect of natural feeding of Daphnia magna and silk worms on the absolute weight growth of pearl catfish (Clarias gariepinus) seeds aged 5 days. The method used is an experimental method that aims to determine the effect of feeding Daphnia sp and silk worms on the absolute weight growth of pearl catfish seeds (Clarias gariepinus) aged 5 days in a controlled environment. This study was arranged in a completely randomized design (CRD) with 3 (three) treatments and each consisting of 9 (nine) repetitions, thus there were 27 experimental units. Treatment A 100% silk worm (control), treatment B: 100% Daphnia sp and treatment C 50% Daphnia sp and 50% silk worm. The parameter observed was absolute weight growth. The results showed that the highest absolute weight growth was obtained from treatment A at 1.22 g, then treatment C at 0.76 g and the lowest was treatment B at 0.33 g. Based on the LSD further test, all feed treatments had significant differences on the absolute weight of fish fry. Based on the LSD further test as a whole shows that all feed treatments have significant differences on the absolute weight of fish seeds.